S100A7 as a potential diagnostic and prognostic biomarker of esophageal squamous cell carcinoma promotes M2 macrophage infiltration and angiogenesis. Issue 7 (8th July 2021) - Lu, Zhiliang; Zheng, Sufei; Liu, Chengming; Wang, Xinfeng; Zhang, Guochao; Wang, Feng; Wang, Sihui; Huang, Jianbing; Mao, Shuangshuang; Lei, Yuanyuan; Wang, ZhanYu; Sun, Nan; et al.
Abstract: Dysregulated expression of S100A7 is found in several cancers and plays an important role in tumor progression; however, its carcinogenic role in esophageal squamous carcinoma (ESCC) is still poorly understood. Here, we identified that the levels of S100A7 were remarkably upregulated in 341 tumor tissues ( P < .001) and 274 serum samples ( P < .001) of ESCC patients compared with normal control. It was an independent prognostic factor ( P = .026). Furthermore, a new diagnostic model for ESCC based on serum S100A7, SCC, and crfra21‐1 was established with area under curve (AUC) up to 0.863 (95% CI: 0.802‐0.925). Mechanically, we found upregulated S100A7 could promote cell migration and proliferation through intracellular binding to JAB1 and paracrine interaction with RAGE receptors and then activates the downstream signaling pathways. In addition, exocrine S100A7 could promote M2 macrophage infiltration and polarization by up‐regulating M2 macrophage associated proteins, and tumor angiogenesis by enhancing the activation of p‐ErK and p‐FAK pathways. Further animal experiments confirmed the role of S100A7 in promoting M2 macrophage infiltration and angiogenesis in ESCC. In conclusion, these findings highlighted the potential diagnostic and prognostic value of S100A7 in patients with ESCC. Meanwhile, our results reveal that S100A7 promotes tumor progression by activating oncogenic pathways and remodeling tumor microenvironment, which paving the way for the progress of S100A7 as a therapeutic target for cancer treatment. Abstract : Elevated S100A7 in tumor tissues and serum samples of ESCC patients suggest a role as a biomarker. A novel and promising diagnostic model for ESCC based on serum S100A7, SCC, and crfra21‐1 was established. S100A7 promotes tumor progression by activating oncogenic pathways and remodeling tumor microenvironment.